ANALYSIS OF THE IMPACT OF CONTRIBUTION ASSISTANCE FOR THE NATIONAL HEALTH INSURANCE PROGRAM ON THE UTILIZATION OF HEALTH SERVICES BY THE POOR IN THE REGENCIES/CITY OF BALI PROVINCE - Ketut Valentina; Anak Agung Istri Ngurah Marhaeni (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The JKN-PBI program was introduced as a government initiative to ensure access to health services for the poor and underprivileged. However, its implementation still faces several challenges, resulting in suboptimal utilization. These conditions necessitate a comprehensive analysis of the various factors influencing the program’s effectiveness. This study aims to analyze both the simultaneous and partial effects of contribution assistance, JKN-PBI participation, and health facility availability on the utilization of health services by the poor in the regencies/city of Bali Province. It also investigates differences in health service utilization between poor populations in Denpasar City and other regencies in Bali Province, as well as measures the satisfaction level of JKN-PBI participants with the healthcare services they receive. A quantitative approach is employed using both associative explanatory and comparative methods. A total of 45 panel data entries were analyzed using multiple linear regression, regional differences were assessed with a paired t-test, and satisfaction levels were measured among 30 JKN-PBI participants in Denpasar City using the SERVQUAL Model. The results show that, collectively, contribution assistance, JKN-PBI participation, and health facilities significantly affect health service utilization. However, on a partial basis, only health facilities have a positive and significant impact, while the other two variables do not show a significant effect. Denpasar City demonstrates a significantly higher utilization rate compared to other regencies in the province. The satisfaction level of JKN-PBI participants regarding access to health services is categorized as high, as reflected by respondents from Denpasar City.